Relevansi Kurikulum Merdeka dalam Kegiatan Belajar Mengajar di MA Darul Falah Sumbergempol terhadap Perspektif Ta`Lim Muta`Alim - Rizal Huda Hizbullah; Muhamad Sidiq Asyhari (Departement of Mathematics Education, 2024)
This study aims to explore the relevance of the Merdeka Curriculum in the teaching and learning activities at MA Darul Falah Sumbergempol, drawing upon the perspective of ta'lim mutaalim. The Merdeka Curriculum, as the latest innovation in the Indonesian education system, is designed to encourage students to be more proactive and independent in the learning process. The research also investigates the alignment between formal and non-formal education implemented by MA Darul Falah Sumbergempol, with the principles of learning inherent in the Merdeka Curriculum and ta'lim mutaalim. The research method used is a qualitative descriptive approach, involving data collection through observation, interviews, and documentation analysis. The findings indicate a strong correlation between the implementation of the Merdeka Curriculum and the learning concepts in ta'lim mutaalim. These findings include the enthusiasm for seeking knowledge, increased creativity, promotion of tolerance, fostering a sense of community, respectful behavior of students towards teachers, and the development of student autonomy in the learning process. Thus, this study asserts that the Merdeka Curriculum is not in conflict with the learning principles found in the ta'lim mutaalim. Instead, the Merdeka Curriculum can serve as an effective complement to strengthen existing learning concepts, and provide a more solid foundation for inclusive, value-based education.